Vacuum arc deposition and microstructure of ZrN-based coatings - Travitzky, Nahum; et al. (Surface & Coatings Technology, 1997)
Thin coatings of ZrN, and bilayer coatings TiN/ZrN and ZrN/TiN of up to 3 μm thickness were deposited using a triple-cathode vacuum arc plasma gun connected to a straight plasma duct, where an axial magnetic field was imposed. The substrates were cemented carbide bars, having a composition of 90% WC, 1.8% TaC, 0.2% NbC, and 8% Co. The coatings were deposited with an arc current of 200 A, background nitrogen pressure of 0.4-2 Pa, substrate temperatures of 200 to 600°C, and substrate bias voltages in the range of 0 to -200 V. The magnetic field in the duct was in the range of 1 to 10 mT. The structure and composition of the coating and interface morphology were studied by means of X-ray diffraction, Auger electron spectroscopy, transmission electron microscopy and scanning electron microscopy combined with energy dispersive spectroscopy analyses. It was shown that for nitrogen pressures higher than 0.4 Pa a single-phase ZrN coating with a NaCl-type structure was obtained. The microstructure of the ZrN coatings and ZrN and TiN layers of the bilayer coatings was found to be composed of (111) oriented columnar grains, although near the coating-substrate interface randomly oriented grains were also observed. In the bilayer coatings a sharp interface without intermixing between the TiN and ZrN layers was observed. The preferred grain orientation was independent of the substrate bias voltage and temperature. However, the coating grain size increased with the substrate temperature and decreased with the substrate bias voltage. It was shown that Co diffused from the cemented carbide substrate to the free surface of the coating, and its concentration there increased with the deposition temperature. © 1997 Elsevier Science S.A.
Keywords: Microstructure; Texture coefficients; Vacuum arc deposition; ZrN coating